2020
DOI: 10.1136/gutjnl-2020-321918
|View full text |Cite
|
Sign up to set email alerts
|

WASh multicentre randomised controlled trial: water-assisted sigmoidoscopy in English NHS bowel scope screening

Abstract: ObjectivesThe English Bowel Cancer Screening Programme invites 55 year olds for a sigmoidoscopy (Bowel Scope Screening (BSS)), aiming to resect premalignant polyps, thus reducing cancer incidence. A national patient survey indicated higher procedural pain than anticipated, potentially impacting on screening compliance and effectiveness. We aimed to assess whether water-assisted sigmoidoscopy (WAS), as opposed to standard CO2 technique, improved procedural pain and detection of adenomatous polyps.DesignThe WASh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
1
1
1
Order By: Relevance
“…Its advantages include lower cost and risk compared with colonoscopy and a more limited bowel preparation. Its disadvantages include a lower protection against right-sided colon cancer, and in case of unsedated procedures, as is usually planned in population-based screening programs,[ 1 2 3 4 5 6 24 ] a low satisfaction experience for patients, as our study confirmed.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Its advantages include lower cost and risk compared with colonoscopy and a more limited bowel preparation. Its disadvantages include a lower protection against right-sided colon cancer, and in case of unsedated procedures, as is usually planned in population-based screening programs,[ 1 2 3 4 5 6 24 ] a low satisfaction experience for patients, as our study confirmed.…”
Section: Discussionsupporting
confidence: 73%
“…Our observations seem to support in part the results of a recent multicenter CRC screening sigmoidoscopy trial conducted within the English Bowel Scope Screening. [ 24 ] However, in our study, we found some differences that deserve consideration. Our data show that BBPS was comparable between groups, this notwithstanding lesion detection [ Table 2 ] was higher (even if comparable) in the WIS group than in the CO 2 S group.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation